The STRATEGI KOMUNIKASI PEMBANGUNAN DALAM IMPLEMENTASI KONSEP SMART ENVIRONMENT DI KOTA CIREBON: DEVELOPMENT COMMUNICATION STRATEGY IN THE IMPLEMENTATION OF THE SMART ENVIRONMENT CONCEPT IN CIREBON CITY - Fifi Novianty (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2021)
This journal examines the development communication strategy in implementing the smart environment concept in the city of Cirebon. The concept smart environment focus refers to how a city is managed and refers to development that is environmentally friendly and does not damage the ecosystem. The research methodology uses a systematic literature review, the focus of the research is examining the concept of smart environment in the city of Cirebon. The results showed that the existence of a development communication strategy in implementing the smart city program, especially in the concept of smart environment in the city of Cirebon, provides convenience in implementing the program. The development communication strategy used in the Cirebon city smart environment concept is 1.) Looking at the Targets. 2.) Social Mobilization. 3.) To Secure Understanding. 4.) To Establish Acceptance. 5.) To Motivate Action. Thus, the role of development communication in implementing the smart environment concept can be more focused, and optimize the achievement of the goals to be achieved, because it has a more structured and directed development communication strategy.